High-field electron spin resonance spectroscopy study of GdFeAsO1−xFx superconductors - Alfonsov, Alexey; Murányi, F.; Kataev, V.; Lang, G.; Leps, N.; Wang, L.; Klingeler, Rüdiger; Kondrat, A.; Hess, C.; Wurmehl, S.; Köhler, A.; Behr, G.; et al. (Physical review. B, Condensed matter and materials physics, 2011)
We report a detailed investigation of GdO1−xFxFeAs (x=0, 0.07, and 0.14) samples by means of high-field and high-frequency electron spin resonance (HF-ESR) together with measurements of thermodynamic and transport properties. The parent GdOFeAs compound exhibits Fe long-range magnetic order below 128K, whereas both doped samples do not show such order and are superconducting with Tc=20 K (x=0.07) and Tc=45 K (x=0.14). The Gd3+ HF-ESR reveals an appreciable exchange coupling between Gd and Fe moments, through which the static magnetic order is clearly seen in the parent compound. Owing to this coupling, HF-ESR can probe sensitively the evolution of the magnetism in the FeAs planes upon F doping. It is found that in both superconducting samples, where the Fe long-range order is absent, there are short-range, static on the ESR time scale magnetic correlations between Fe spins. Their occurrence on a large doping scale may be indicative of the ground states’ coexistence.
Im Titel ist die Zahl 1, das Zeichen - und der Buchstabe x jeweils tiefgestellt
Gesehen am 01.03.2022